Rapid Synthesis of Graphene Oxide Derived from Biomass with Atmospheric Plasma Technology - Airine Hijrah Handayani; Arbi Dimyati; Abdul Waris; Raden Ibrahim Purawiardi; Muflikhah Muflikhah; Elita Vegy Noviantana; Firda Amalia; Rohmad Salam (Journal of Mathematical and Fundamental Sciences)
In this study, we explored a low-cost, green, and renewable approach utilizing biomass resources, i.e., coconut fronds, palm fronds, and rambutan stems, to rapidly synthesize graphene oxide via atmospheric plasma techniques. The plasma treatment, with argon gas as the plasma source and a power source of 960 W, lasted for 5 minutes. Graphene oxide (GO) was confirmed using SEM and TEM images with a C:O content ratio greater than 80% for all samples and the formation of graphene layers. The presence of a D-band and a G-band in Raman spectroscopy as well as O-H and C-O groups in the FTIR confirmed the existence of GO.